Perbaikan Line Balancing Proses Packing Tablet XYZ Menggunakan Metode Ranked Positional Weight di PT. Y - Hana Sekar Ayu Edy purwanto; Rahmaniyah Dwi Astuti (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2019)
PT. Y is a company in the pharmaceutical industry that produces finished drugs. Based on observations in the packing process of Tablet XYZ products, it is still found that there are bottlenecks between work stations caused by a lack of equal distribution of work. Work stations whose workload is not evenly distributed, can cause the low of line efficiency. This study improved line balancing using the Ranked Positional Weight method which aims to increase the line efficiency value of the Tablet XYZ packing process. The result of this study is an increase in the value of line efficiency after the distribution of work elements is evenly distributed.